Strategic Climate Investment Partnership Roundtable - Chevallier, Romy; Chesterman, Sabrina (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
On 6 February 2022, the African Union’s (AU's) Climate Change and Resilient Development Strategy and Action Plan (2022-2032) was endorsed at the 35th Ordinary Session of the AU’s Assembly of African Heads of State and Government. This is Africa’s first collective climate change action plan and Strategy that details specific suggested actions the continent needs to urgently achieve to respond to climate change. Subsequently, on the 19-20 June 2023, the AU hosted a Strategic Climate Investment Partnership Roundtable in Addis Ababa, Ethiopia. The objective of the Roundtable was to leverage partnerships and align investment opportunities to support the operationalisation of the Strategy. This is the facilitation slide deck for the Roundtable. It covers the objectives of the Roundtable, the intended outcomes, principles and a session overview. It then provides information on the Strategy including its rationale, vision, goal, objective and alignment with global frameworks. It gives an overview of the Strategy and how it was developed, including the consultation process. It then addresses the implementation of the Strategy, the outcomes of operationalisation meetings to date and how to enhance the enabling environment. It highlights the need for partnerships and areas where support is required. The Strategy is then presented in more detail, looking at the intervention axes and key focal areas. It emphasises the need for transformative investments providing opportunity for working group discussions and feedback. The presentation concludes with the identification of next steps, policy alignment and the programmatic development process.